DISCUSSIONS ABOUT ESSENCE OF LAW IN THE DISCOURSE ON LAW AND ORDER - TOKARYEV, Vasily (Comparative Legilinguistics, 2010)
The article is devoted to the ontological structure of law. The contradictions between its various interpretations are eliminated in the law and order discourse. He allows to reveal the social bases of law – the legal situations resolved by the legitimate instance. The law and order discourse is formed in a context of political and legal doctrines of the epoch of the Enlightenment. They raised a question about the universal character of legal structure and offered a new methodology of its comprehension. Subsequently V.S. Nersesyanc interpreted this discourse in an original way. However in the beginning of the XX-th century the weaknesses of the discourse of law and order became the reason of crisis of sense of justice. The conception of ―political theology‖ by C. Schmitt who criticized the liberal jurisprudence was the answer to it. At the same time a rivalry between points of view within the limits of a uniform scientific discourse brings to light its such essential component as a free discussion. Nevertheless, the discussion about essence of law is artificial narrowed by the considerable influence of the political sphere on the legal sphere.